Positive correlations between TyG and TyG-BMI indices and the risk of NAFLD and degree of liver fibrosis in patients undergoing PCI - Chen, Yingxiang; Wang, Che; Du, Xiaoyu; Sun, Xiaotong; Song, Wenjuan; Lu, Chengzhi (Frontiers in Endocrinology, 2025)
BackgroundWe aim to investigate the association between TyG(Triglyceride-Glucose index) and TyG-BMI(Triglyceride-Glucose-Body Mass Index) indices and the risk of non-alcoholic fatty liver disease (NAFLD) in patients undergoing percutaneous coronary intervention (PCI), an area where their predictive value is currently unclear, despite their established link to insulin resistance, metabolic syndrome, and cardiovascular disease.MethodsIn this cross-sectional study, 776 patients who underwent coronary angiography and PCI were categorized into NAFLD+PCI and PCI groups based on abdominal ultrasound. They were further classified by TyG and TyG-BMI indices. Continuous variables were compared using ANOVA, Wilcoxon-Mann-Whitney, or t-tests, while categorical variables were analyzed with χ² or Fisher exact tests. Logistic regression identified independent factors for NAFLD in PCI patients. ROC curves evaluated the predictive efficacy of TyG and TyG-BMI for NAFLD. Linear correlation and multiple linear regression assessed relationships among NAFLD fibrosis score (NFS), TyG, and TyG-BMI.ResultsAmong 776 patients, NAFLD was detected in 305. After adjusting for age, smoking, hypertension, diabetes, sex, and cardiovascular disease, multivariate logistic regression showed the TyG index was a significant risk factor for NAFLD in PCI patients (OR = 2.04; 95% CI, 1.62-2.55; P < 0.001). Similarly, the TyG-BMI index, total cholesterol, triglycerides, LDL cholesterol, fasting blood glucose, and BMI were associated with increased NAFLD risk. Each unit increase in the TyG index raised the NAFLD risk by 2.63-fold (OR = 2.63; 95% CI, 1.78-3.8; P<0.001), and each unit increase in the TyG-BMI index by 3.80-fold (OR = 3.80; 95% CI, 2.55-5.68; P < 0.001). Multivariate linear regression indicated that in the PCI-NAFLD group, each unit increase in the TyG index increased the NFS value by 0.247 (β = 0.247; 95% CI, 0.19-0.45; P < 0.001), and each unit increase in the TyG-BMI index increased the NFS value by 0.344 (β = 0.344; 95% CI, 0.28-0.59; P < 0.001).ConclusionsThe TyG index and TyG-BMI were positively associated with the risk of NAFLD in patients treated with PCI, reflecting the severity of liver fibrosis.